The Latent Profile Analysis on Stress of Women managers - Joo, Jaehong; Jo, Hyeonah; Kim, Yesuh; Song, JiHoon (Korean Journal of Industrial and Organizational Psychology, 2023)
This study aims to emphasize the necessity of exclusive stress management intervention to solve women managers’ stress by exploring the latent stress profile. It is needed to scrutinize stress factors faced by women managers who suffered from the double burden of taking roles in the workplace and at home. We conducted a latent profile analysis to scrutinize the stress types among women managers. First, we significantly derived four profiles depending on the extent of their work and home stress. Second, in the predictor variable, age, the rate of women workers in their teams, and the perception of their supervisors’ gender equality was significantly influenced by the probability of belonging to each profile, while spouses’ employment was insignificant. Finally, in outcome variables, the low profiles for both work and home stress were significantly more satisfied with their personal, family, and professional life than the rest of the profiles. Moreover, they positively perceived the women managers’ overall professional life. based on the results, we provided theoretical and practical implications and discussed research limitations and directions for further research.